Dysregulated TFEB–autophagy-lysosome pathway links acute COVID-19 immunopathology to Long COVID sequelae - Gabig-Cimińska, Magdalena (Frontiers in Immunology, 2025)
SARS-CoV-2 disrupts cellular homeostasis, including the autophagy-lysosome pathway (ALP), a critical component of innate immunity and viral clearance. By subverting autophagy, SARS-CoV-2 proteins such as ORF3a, ORF7a, and NSP6 inhibit autophagosome-lysosome (APG-L) fusion, generating “incomplete autophagy” that permits viral persistence and drives hyperinflammation. Transcription factor EB (TFEB), a master regulator of lysosomal biogenesis and autophagy, has emerged as a central player in the host response to coronavirus infection. TFEB orchestrates the expression of genes required for lysosomal function and autophagic flux while also shaping immune processes, including cytokine production, interferon-stimulated gene expression, and inflammasome clearance. This mini review synthesizes current knowledge on the TFEB-ALP axis in COVID-19 pathogenesis, highlighting its influence on acute immunopathology and its potential contribution to post-acute sequelae (Long COVID). Restoring TFEB activity and autophagic flux may counteract SARS-CoV-2 evasion strategies and restrain aberrant inflammatory responses. Harnessing the TFEB-autophagy pathway as a host-directed therapeutic strategy could help rebalance immune homeostasis, limit tissue damage during acute infection, and mitigate persistent inflammatory sequelae in Long COVID.